Classical Arabic philology and poetry : a bibliographical handbook of important editions from 1960-2000 - Weipert, Reinhard (Handbuch der Orientalistik. Nahe und der Mittlere Osten, 2002)
This concise bibliography is a comprehensive list of Classical Arabic texts on grammar, lexicography, adab, balagha, metrics and poetry, which have been edited from 1960 to 2000.